15 What Influences Loss of Appetite in Older People? A Qualitative Study. (16th March 2021) - Cox, N J; Ibrahim, K; Morrison, L; Robinson, S M; Roberts, H C
Abstract: Introduction: Appetite loss in older people is common and associated with malnutrition, sarcopenia and frailty. Management of appetite loss may prevent these health burdens but currently no effective clinical interventions exist. This is partly due to lack of knowledge about influences on appetite perceived by older individuals. These views may provide novel avenues for intervention on appetite loss. Aim: To understand older individual's perceptions of influences on appetite loss. Method: Semi-structured qualitative interviews with men and women aged ≥65 years, living in their own home, were audio-recorded and transcribed. Reflexive thematic analysis, with inductive coding, generated themes with data examples. Results: 13 individuals (8/13 female, 4/13 living alone) were recruited. Accounts of influences on appetite were grouped into three themes: physical, psychological and external factors. The physical theme related to a physical state of ageing, using energy and being active, and physical symptoms, illness and treatment. The psychological theme explained the influence of mood or wellbeing, the appeal of food, and reward in the activity of cooking. External factors related to influences of other people, coping with life experiences and transitions, and perceptions of health. Influences were perceived to impact on appetite loss in distinct ways, via a physical feeling of fullness (physical theme), or creating a negative experience with food and eating (psychological and external themes). Individuals tended to have either a physical or psychological focus. Importantly, illness and its treatment impacted on both appetite loss narratives. Conclusions: A number of influences on appetite are described by older individuals, relating to their physical and psychological self, and social and environmental factors. These seem to impact on appetite loss in distinct ways, by precipitating either a physical feeling of fullness, or a negative experience with food and eating. Identifying factors affecting an individual's appetite could facilitate person-centred approaches to management.